The evolution of flexibility and function in the Fc domains of IgM, IgY, and IgE - Calvert, Rosaleen A.; Nyamboya, Rosemary A.; Beavil, Andrew J.; Sutton, Brian J. (Frontiers in Immunology, 2024)
Antibody Fc regions harbour the binding sites for receptors that mediate effector functions following antigen engagement by the Fab regions. An extended "hinge" region in IgG allows flexibility between Fab and Fc, but in both the most primitive antibody, IgM, and in the evolutionarily more recent IgE, the hinge is replaced by an additional domain pair in the homo-dimeric, six-domain Fc region. This permits additional flexibility within the Fc region, which has been exploited by nature to modulate antibody effector functions. Thus in pentameric or hexameric IgM, the Fc regions appear to adopt a planar conformation in solution until antigen binding causes a conformational change and exposure of complement binding sites. In contrast, IgE-Fc principally adopts an acutely bent conformation in solution, but binding of different receptors is controlled by the degree of bending and there is allosteric communication between receptor binding sites. We trace the evolution of Fc conformational diversity from IgM to IgE via the intermediate avian IgY, by studying the solution conformations of their Fc regions by small-angle X-ray scattering. We compared four extant proteins: human IgM-Fc homo-dimer, chicken IgY-Fc, platypus IgE-Fc and human IgE-Fc. These are proteins that first appeared in the clades jawed fish (425 million years ago (mya)), tetrapods (310 mya), monotremes (166 mya) and hominids (2.5 mya) respectively. We analysed the scattering curves in terms of contributions from a pool of variously bent models chosen by a non-negative linear least-squares algorithm, and found that the four proteins form a series in which the proportion of acutely bent material increases: IgM-Fc < IgY-Fc < plIgE-Fc < huIgE-Fc. This follows their order of appearance in evolution. For huIgM-Fc homo-dimer, while none is acutely bent, and a significant fraction of the protein is sufficiently bent to expose the C1q binding site, it predominantly adopts a fully extended conformation. In contrast, huIgE-Fc is found principally to be acutely bent, as expected from earlier studies. IgY-Fc, in this first structural analysis of the complete Fc region, exhibits an ensemble of conformations from acutely bent to fully extended, reflecting IgY's position as an evolutionary intermediate between IgM and IgE.